Comparison of Child Sexual Abuse Knowledge and Attitude Levels of Parents of Special Needs Children with Normally Developing Children - KAÇAN, Havva; GÜMÜŞ, Funda; YILDIZ, Eren (Current Approaches in Psychiatry, 2023)
This study aimed to compare parents' knowledge and attitudes of children with special needs and normally developing children about child sexual abuse. The study was cross-sectional, descriptive, and correlational design, and the sample consisted of 228 parents, including 153 parents of normal children and 75 parents of children with special needs. Personal Information Form and Child Abuse Knowledge/Attitude Scale for Parents were used to collect the data. The only independent variable with explanatory power on the level of Child Abuse Knowledge and Attitude was found to be educational status. In the model created with this variable, educational status explained 2.9% of the variation on the total score of the Child Abuse Knowledge and Attitude Scale. Ninety-four point eight percent of the parents had no previous education about sexual abuse against children but were informed about it. Parents' knowledge and attitudes towards sexual abuse were significantly affected by the educational status of the parents. In this context, awareness should be increased through school-based programs organized by mental health professionals.
Keywords: Psychiatry; Eğitim; Özel; knowledge; child; Sosyal Çalışma; RC435-571; sexual abuse; parent; Psikoloji; attitude; Aile Çalışmaları; Sağlık Politikaları ve Hizmetleri; 3. Good health; 5. Gender equality